Gimme a call - Mlynowski, Sarah (LOndon : London, 2010)
After accidentally dropping her cell phone into a fountain at the mall, fourteen-year-old Devi Banks starts to get phone calls--and an earful of advice on how to live her life to avoid making disastrous choices--from her seventeen-year-old self.
Keywords: Conduct of life -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Telephone -- Juvenile fiction; Conduct of life -- Fiction; Dating (Social customs) -- Fiction; High schools -- Fiction; Schools -- Fiction; Telephone -- Fiction; Conduct of life -- Fiction; Dating (Social customs) -- Fiction; High schools -- Fiction; School stories; Telephone -- Fiction